2020
DOI: 10.1097/mnm.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

Empirical 188Re-HDD/lipiodol intra-arterial therapy based on tumor volume, in patients with solitary inoperable hepatocellular carcinoma

Abstract: Objective This study aimed to assess the potential benefits and tolerability of an empirical dose of approximately 0.8–1.2 mCi (29.6–44.4 MBq) of 188Re-4-hexadecyl-1-2,9,9-tetramethyl-4,7-diaza-1,10-decanethiol/lipiodol (188Re-HDD/lipiodol) per milliliter of tumor volume, administered after super-selection of the tumor feeding branches of hepatic artery for treatment of inoperable hepatocellular carcinoma (HCC). Methods Patients with advanced HCC or cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Targeting smaller lesions than the ones that have been targeted in this Phase 1 study appears to be another option to increase efficacy. Using the criteria of the European Association of Study of the Liver, Shinto et al reported a 90% response rate, in a study with a mean lesion size of 6.6 cmin, in comparison with 8.9 cm in Lip-Re-1, while using a mean activity of 2 GBq of 188 Re-HDD lipiodol [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting smaller lesions than the ones that have been targeted in this Phase 1 study appears to be another option to increase efficacy. Using the criteria of the European Association of Study of the Liver, Shinto et al reported a 90% response rate, in a study with a mean lesion size of 6.6 cmin, in comparison with 8.9 cm in Lip-Re-1, while using a mean activity of 2 GBq of 188 Re-HDD lipiodol [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients received intra-arterial injection of 188 Re-SSS lipiodol into the hepatic artery under local anesthesia using the classical Seldinger technique, with a whole liver approach, as classically applied with 131 I lipiodol. 188 Re-SSS lipiodol was locally prepared as previously described [ 10 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next radionuclides in terms of aggregated research output were rhenium-186 ( 186 Re), rhenium-188 ( 188 Re), strontium ( 89 Sr), and samarium-153 ( 153 Sm), which have—together with other radionuclides—been used in palliative treatment of bone metastases or radiosynovectomy [ 26 , 27 ]. 188 Re has, in recent years, been explored both for melanoma, in a radioimmunoconjugate, and for inoperable hepatocellular carcinoma, with selective administration of [ 188 Re]Re-4-hexadecyl-1-2,9,9-tetramethyl-4,7-diaza-1,10-decanethiol/lipiodol [ 28 , 29 ].…”
Section: Trendsmentioning
confidence: 99%
“…A multi-centric study by nuclear medicine departments in India and Vietnam found complete/partial disappearance of tumor or stable disease in [ 68% of patients and survival rates of 58% at 24 months and 30% at 36 months, with a median survival of 980 days [99]. A more recent study showed the utility of 188 Re-HDD/lipiodol for therapy in patients with solitary HCC not amenable to resection [102]. Moreover, post-administration SPECT imaging could be used to assess absorbed doses in target and normal tissue [103].…”
Section: Radionuclide-tagged Formulations Of Lipiodolmentioning
confidence: 99%